Analisis Akuntabilitas dan Transparansi Sistem Pengelolaan Dana Zakat dan Infak di Wahdah Inspirasi Zakat (WIZ) Kabupaten Bone Berdasarkan PSAK 109 - Fadillah, Nur; Fajerin, Nur; Hasbi, Hartas (Jurnal Serambi Ekonomi dan Bisnis, 2024)
This research aims to activate the effectiveness of the zakat and infaq fund management system at Wahdah Inspirasi Zakat in Bone Regency by referring to the PSAK 109 standard, with the main focus on identifying and analyzing fund management practices, financial mixing, and institutional accountability mechanisms. Issues that will be discussed include the level of institutional compliance with PSAK 109 standards, transparency in fund management, and mechanisms for distributing zakat and infaq. The research method uses a qualitative descriptive approach with data collection techniques through in-depth analysis, direct observation and financial documentation. The research results show that Wahdah Inspiration Zakat has implemented most of the principles of PSAK 109 quite well, but there are still several aspects that require improvement, such as the accounting recording system, financial reporting mechanisms, and transparency in the distribution of zakat and infaq funds, so that institutional capacity development and increasing human resource competency to achieve more effective and accountable fund management in accordance with PSAK 109 standards.